An investigation into South Africans performing online erotic labour, experiences of their labour and their experiences and negotiations of stigmatisation - Megannon, Tegwyn (African Studies, 2025)
The lived experiences of online erotic labourers, in South Africa, is investigated in this dissertation. To investigate the experiences of digital labour and stigma, five South Africans who have performed erotic labour participated in semi-structured interviews. A qualitative research design, grounded in critical theory, was used to develop a rich understanding of online erotic labour. Sex work and erotic labour has been conceptualised through a sex work inclusionary feminist academic lens and analysis was done using reflexive thematic analysis technique. Findings revealed that experiences of erotic labour are significantly influenced by the type of digital platform used to sell labour. These experiences were found to be located within the broader context of platform mediated gig work, and I investigated how platform capitalism affects workers' experiences of precarity. Congruent with other non- stigmatised gig workers, findings show that performing online erotic labour is subject to general forms of income insecurity and economic liability. However, the stigmatised nature of erotic labour creates a unique kind of precarity that is not endemic to all forms of platform mediated gig work. The findings detail how this stigma is navigated and how my participants create positive meanings in their lives related to their erotic labour.